The Influence of Leadership and Empowerment on the Competence and Work Achievement of Teachers in the Office of the Ministry of Religion of Cirebon Regency - Mualim (GoAcademica Research & Publishing, 2022)
Without leadership, a school will suffer a setback. Teachers' competency and work performance would be enhanced through the development of latent potential. Consequently, the purpose of this study is to investigate the impact of leadership and empowerment on the competence and work performance of instructors in the Ministry of Religion, Cirebon Regency. Quantitative technique employing descriptive analysis is used to determine respondents' impressions of research variables. In addition, this study employs Structural Equation Modeling (SEM) with a variance-based approach and Partial Least Squares to evaluate the hypothesis (PLS). (1) Leadership had a positive and statistically significant effect on teacher competence, (2) Empowerment had a positive and statistically significant effect on teacher competence, (3) Leadership had no effect on teacher work performance, and (4) Empowerment had a positive and statistically significant effect on teacher work performance, (5) Competence has a strong and favorable impact on teacher work performance.